2009
DOI: 10.3324/haematol.2009.010835
|View full text |Cite
|
Sign up to set email alerts
|

Association of functional polymorphisms of the transforming growth factor B1 gene with survival and graft-versus-host disease after unrelated donor hematopoietic stem cell transplantation

Abstract: BackgroundMany genetic factors play major roles in the outcome of hematopoietic stem cell transplants from unrelated donors. Transforming growth factor β1 is a member of a highly pleiotrophic family of growth factors involved in the regulation of numerous immunomodulatory processes. Design and MethodsWe investigated the impact of single nucleotide polymorphisms at codons 10 and 25 of TGFB1, the gene encoding for transforming growth factor β1, on outcomes in 427 myeloablative-conditioned transplanted patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The A/A, T/A, and T/T IFN-genotypes for base -874 have been reported to correspond to low, intermediate, and high in vitro cytokine production, respectively [59][60][61][62][63][64]. According with the data already reported, we confirmed that the frequency of the hypersecreting genotype T/T of the IFN-was most over represented in the AA population compared to controls [39,58]. By contrast, there were no significant differences in the polymorphism of IFN-at position +874 between all MDS and each subgroup of MDS patients and healthy controls.…”
Section: Discussionsupporting
confidence: 95%
“…The A/A, T/A, and T/T IFN-genotypes for base -874 have been reported to correspond to low, intermediate, and high in vitro cytokine production, respectively [59][60][61][62][63][64]. According with the data already reported, we confirmed that the frequency of the hypersecreting genotype T/T of the IFN-was most over represented in the AA population compared to controls [39,58]. By contrast, there were no significant differences in the polymorphism of IFN-at position +874 between all MDS and each subgroup of MDS patients and healthy controls.…”
Section: Discussionsupporting
confidence: 95%
“…the myeloablative cohort, as we have previously observed in UD HSCT. 31 It is well recognized that this highly toxic conditioning produces an inflammatory scenario known as 'cytokine storm'. 36,37 In a murine model, the conditioning regimen did alter the contribution of CD8+ or CD4+ subsets to the total FOXP3+ pool with functional importance in defining transplant outcome and are important for protection from GvHD.…”
Section: Discussionmentioning
confidence: 99%
“…30 We have previously published an association of +29C4T SNP and HSCT from unrelated donors (UD). 31 Patients with +29CC genotype experienced a higher non relapse mortality (NRM) and reduced overall survival (OS) compared with the TC and TT genotypes. The impact of this polymorphism on the outcome of sibling donor HSCT is on debate as several studies have given conflicting results, especially in aGvHD.…”
Section: Introductionmentioning
confidence: 99%
“…Further screening for herpes simplex virus, Epstein‐Barr virus, and adenoviruses may also be required in addition to screening for cell type‐ and location‐specific viruses [140]. Genotype screening for donor cells has also been suggested [141], with some reports of specific genetic polymorphisms associated with differential GVHD severity and outcome in allogeneic HSC transplants [142, 143].…”
Section: Preclinical and Clinical Assessmentmentioning
confidence: 99%